Variações espaciais na estrutura da assembleia de peixes do baixo rio Araguaia durante um ciclo hidrológico - Orsi, Carlos Henrique (2012)
The region of the lower Araguaia River is influenced by a flood pulse that causes changes in the environment. This study aimed to identify the spatial effects (main river and tributaries) on the assembly structure of fish. Samples were taken every two months between March and September 2009, at 14 sites (7 in the Araguaia River and 7 in tributaries), fishes were collected with gill nets exposed for 24 hours, for the analysis effort was standardized and indexed in catch per unit of effort in number and biomass, then the attributes of the assembly and the total abundance were set and spatial distribution patterns were identified through factorial analysis. The beta diversity was estimated as the rate of renewal of species. An ordination analysis indicated the formation of three axes and their scores were retained for a PerManova analysis. Analysis of the indicator species was performed to determine if there were local indicator species. Species richness and abundance of fish were higher in the channel of the Araguaia River during the dry season. The diversity in the channel of the Araguaia River in low water seasons and dry seasons differed from the tax on water and flood in relation to the abundance in number of individuals and beta diversity showed that the Araguaia River and tributaries have their assemblages in a non-random status. The evenness showed no significant differences between sites and seasons. The evaluation of indicator species identified a number of species that stick out among the others, mainly in the main channel in the dry season, these facts may be related to environmental changes between seasons, flooding its banks and several structures along the river, providing new habitats and causing some species seek more favorable environments to their needs during the different seasons.